(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article examines the semantics, symbolic meaning, author’s using of colourative black in Basyl Shklyar’s novel “Zalyshenets. Chornyi Voron”. The ways of realization of colourative contrast are outlined.